Investigating the Image of Japanese Food on Intention of Behavior: Indonesian Intention to Visit Japan - Cahyanti, Mega Mirasaputri; Rohman, Fatchur; Irawanto, Dodi (Journal of Indonesian Tourism and Development Studies, 2014)
Country-of-Origin Image (COI) has been recognized as a possible factor to influence the image of product especially toward international products. COI occurred due to the consumer's behavior which uses the nation image on some international products to consider the quality before they build a bearing on the products. The better the country's image in some products, the greater influence and impact will be given to their products image. Many previous studies have been done on COI toward foreign products, focused on the intention behavior. The intention behavior in this study is including a purchase intention or intention to try a product. However, research about its impact in the term of tourism is limited. Moreover, the use of international food as an object is limited as well. This study addressed an insight of tourism impact about Indonesian intention to visit Japan which influenced by image of Japanese food, which given by country's image (Japan). The results showed that the image of Japanese food perceived after they consumed it, significantly influence an intention to visit Japan. Therefore, marketing and promotions of a countries as one entity should focus to use their traditional food (international product for other people from other countries) to promote their country as tourism destination. Keywords: Country of Origin Image (COI), Intention to Visit a Country, International food.